Identifying the Dimensions and Sustainable Supply Chain Operations for Knowledge-Based Decision Making in Iran’s Tax Affairs Organization - Shahidi Bonjar, Hamidreza; Salajegheh, Sanjar; Pourkiani, Masoud; Sayadi, Saeed (International Journal of Supply Chain Management, 2019)
Abstract—This research was conducted by the aim of Identifying the dimensions and sustainable supply chain operations for knowledge-based decision making in the Iran tax affairs organization. From the point of purpose, this study is a fundamental research which is implemented by qualitative research. There is two main part in this study: the first one is about the background and theoretical basics which is related to the dimensions and components of knowledge-based decision making; the second part is a qualitative research that is implemented in a grounded theory methodology. This research’s population concludes experts of tax affairs organization in Iran. That experts has been chosen which have required qualifications and information by the use of purposive sampling method. The process of choosing these experts has continued until reaching the theoretical saturation which ended in 50 interviews. Open, axial and selective coding have been conducted respectively for analyzing the gathered data from interviews. The triangulation and control methods have implemented for confirmation and enhancement of the reliability of findings and interview transcripts. Based on a partial least squares approach, the confirmatory factor analysis method has also conducted for the estimate of indices. Respectively, the confirmatory factor analysis, Path analysis, and Bootstrapping have done in the frame of this approach. Findings of this study show that components of knowledge-based decision making are: 1- performance factor, 2- behavioral factor and 3- attitude factor.